A review on the aroma composition of Vitis vinifera L. Pinot noir wines: origins and influencing factors. Issue 10 (31st May 2021) - Longo, Rocco; Carew, Anna; Sawyer, Samantha; Kemp, Belinda; Kerslake, Fiona
Abstract: Vitis vinifera L. Pinot noir still wines are some of the most popular and expensive red wines in the world. Several research articles are reported in literature concerning the impacts of viticultural and enological practices, and vineyard location, on Pinot noir still wine aroma. This review summarizes the previous and latest literature pertaining to volatile compounds including esters, higher alcohols and C13 -norisoprenoids, and their effect on Pinot noir wine perceived aroma. Their origin and behavior are discussed, as well as their role in regional differentiation. The first part of this review paper presents an overview of volatile compounds that are usually found in Pinot noir still wines at concentrations higher than their odor detection threshold. The second part deals with studies pertaining to human inputs that impact on Pinot noir wine aroma profile such as viticulture and winemaking interventions. The role of the vineyard site is also revised. This review concludes by considering what further opportunities are available to researchers in this field for greater control over Pinot noir wine quality outcomes.